Highly sensitive and selective detection of cadmium with a graphite carbon nitride nanosheets/Nafion electrode. Issue 114 (2nd December 2016) - Gao, Wenyu; Wang, Xiaofang; Li, Pei; Wu, Qiongtao; Qi, Fang; Wu, Songmei; Yu, Yu; Ding, Kejian
Abstract : A sensitive g-C3 N4 Cd 2+ sensor is fabricated in this paper. The linear range and detection limit for Cd 2+ detection could be as low as 1 nM and (0.5 nM). This sensor also has excellent stability and selectivity for Cd 2+ against interferences. Abstract : A highly sensitive and selective electrochemical sensor is developed for the detection of cadmium with a nanosheet graphitic carbon nitride (g-C3 N4 ) modified electrode. The g-C3 N4 nanosheet modified glassy carbon electrode detects heavy metal not only by electrostatic interactions, but also by intercalating the holes during differential pulse anodic stripping voltammetry (DPASV) measurements for Cd 2+ in aqueous solution. The calibration curves for Cd 2+ covered two ranges varying from 1 nM to 1 μM and 1 μM to 100 μM. The limitation of detection (LOD) is estimated to be 0.5 nM for Cd 2+, which is 53 times lower than the guideline values of drinking water given by the World Health Organization (WHO). In addition, the good repeatability and stability of the modified electrode is feasible for heavy metal detection in this study.